Bulgaran Foreign Inteligence Files on International Terrorism - Baev, Jordan (Дриновський збірник, 2024)
The article is based on two new archival sources – the official and operational records of Bulgarian Foreign Intelligence services and the State Security Counterintelligence records. It comprises of three paragraphs, first of which reveals the normative and organizational base of State Security intelligence and counterintelligence activity. The second paragraph discusses the Warsaw Pact intelligence information exchange on international terrorist groups, while the last paragraph summarizes the information of the Bulgarian intelligence files on international terrorism. The comprehensive and critical comparative approach and a careful re-writing of those sensitive document collections throw new light on several disputable questions with adding authentic arguments to some previous views and hypotheses, while denouncing a few others. The Bulgarian Intelligence and Security services were assigned with principal tasks for operations in the “close neighborhood” – the Balkans, Eastern Mediterranean, and the Middle East. Most probably, the collected databases on International Terrorism continued to be in use for operational purposes in the next two decades of the transition era.